2021
DOI: 10.1051/sicotj/2021013
|View full text |Cite
|
Sign up to set email alerts
|

A long-term cross-sectional study with modified forgotten joint score to assess the perception of artificial joint after total knee arthroplasty

Abstract: Background and purpose: The ultimate goal for an arthroplasty surgeon is to provide the patient a joint that feels more like a natural joint. The Modified Forgotten Joint Score (MFJS) is a newly introduced functional scoring system that has a superior ability to assess this property among arthroplasty patients. The objective of this study is to evaluate the long-term temporal association of the MFJS and total knee arthroplasty (TKA). Methods: We assessed 360 patients post TKA with MFJS questionnaire. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Kafelov et al [24] found the FJS score (76.3 ± 13) similar to our study. Chithartha et al [25] found a constant evolution of the mean modified FJS from 64.4 at 3 weeks to 89.9 at 2 years, before a progressive decline to 82.7 at 10 years. Kayani et al [26] noted a significant improvement in the FJS at one-year, two-year, and at five-year follow-ups.…”
Section: Discussionmentioning
confidence: 98%
“…Kafelov et al [24] found the FJS score (76.3 ± 13) similar to our study. Chithartha et al [25] found a constant evolution of the mean modified FJS from 64.4 at 3 weeks to 89.9 at 2 years, before a progressive decline to 82.7 at 10 years. Kayani et al [26] noted a significant improvement in the FJS at one-year, two-year, and at five-year follow-ups.…”
Section: Discussionmentioning
confidence: 98%
“…PROM validation relies on sufficient data and accounting for missing values is an area of contention [ 30 ]. Chithartha et al [ 31 ] and Robinson et al [ 32 ] addressed the missing data in their studies by changing the FJS to the Modified FJS, while others like Rombach et al [ 33 ] choose reasonable estimated data input to correct the information gaps. At 6 months, 10% of patients presenting for follow up did not meet valid JAS score threshold based on survey response input, and at 12 months, 5% of patient inputs did not meet valid JAS threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The goal in joint arthroplasty is for patients to 'forget' the artificial joint, which is indicative of optimal patient satisfaction. Studies have demonstrated improvements in joint awareness and function six months post-TKA (11). However, the relationship between kinesiophobia and joint awareness post-TKA remains underexplored (12).…”
Section: Introductionmentioning
confidence: 99%